Multivariate dynamic analysis of cerebral blood flow regulation in humans - Panerai, R.B.; Simpson, D.M.; Deverson, S.T.; Mahony, P.; Hayes, P.; Evans, D.H. (IEEE transactions on biomedical engineering, 2000)
The contributions of beat-to-beat changes in mean arterial blood pressure (MABP) and breath-by-breath fluctuations in end-tidal CO/sub 2/ (EtCO/sub 2/) as determinants of the spontaneous variability of cerebral blood flow velocity (CBFV) were studied in 16 normal subjects at rest. The two input variables (MABP and EtCO/sub 2/) had significant cross-correlations with CBFV but not between them. Transfer functions were estimated as the multivariate least mean square finite impulse response causal filters. MABP showed a very significant effect in explaining CBFV variability (p<10/sup -11/, Fisher's aggregated-p test) and the model mean square error was significantly reduced (p<0.001) by also including the contribution EtCO/sub 2/. The estimated mean CBFV step response to MABP displayed the characteristic return to baseline caused by the cerebral autoregulatory response. The corresponding response to EtCO/sub 2/ showed a gradual rise taking approximately 10 s to reach a plateau of 2.5%/mmHg. This study demonstrated that spontaneous fluctuations in EtCO/sub 2/ can help to explain the CBFV variability at rest if appropriate signal processing techniques are employed to address the limited power and bandwidth of the breath-by-breath EtCO/sub 2/ signal.